Recurrent ovarian cancer - Chatterjee,J (Oxford University Press, USA, 2015)
Expert comment Within 12 months of completion of chemotherapy, there was recurrent disease evident on Mrs M's CT ... Learning point Recurrent Ovarian Cancer (ROC) 70–90% of patients diagnosed with advanced ovarian cancer will at ...